(3EOGQI GdCReGJ GdeGdjIs - (3gfO(B, (3egOGhjs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2022)
(3GdGSJbQGQ GdeGdj hGdOhQGJ GdGbJUGOjI, GdYhdeI GdeGdjI hYdGbJgG HGdCReGJ GdeGdjI, GdfXQjGJ GdeaSQI ddCReGJ GdeGdjI hCReI GdcSGO GdYXje, GdCReGJ GdfaWjI hCReGJ GdKeGfjfGJ, cPdc CReGJ JSYjfGJ GdbQf GdYTQjf, hCNjQG CReGJ GdbQf GdMGOj hGdYTQjf(B.s
(3eQGLY U(B.131s
Keywords: (3GdCReGJ GdEbJUGOjIs